117k views
5 votes
Sovle the following equation x: 6(4x + 5) = 3(x + 8) + 3​

User Larron
by
5.2k points

2 Answers

1 vote

Answer:


\boxed{\bold{x=-(1)/(7)}}

Equation:


\bold{6\left(4x+5\right)=3\left(x+8\right)+3}

Step By Step Explanation:

  • Expand
    \bold{6\left(4x+5\right): \ 24x+30}
  • Expand
    \bold{3\left(x+8\right)+3: \ 3x+27}


\bold{24x+30=3x+27}

  • Subtract 30 From Both Sides


\bold{24x+30-30=3x+27-30}

  • Simplify


\bold{24x=3x-3}

  • Subtract 3x From Both Sides


\bold{24x-3x=3x-3-3x}

  • Simplify


\bold{21x=-3}

  • Divide Both Sides By 21


\bold{(21x)/(21)=(-3)/(21)}

  • Simplify


\bold{x=-(1)/(7)}


\boxed{\bold{Mordancy}}

User Aristarhys
by
6.0k points
1 vote

Answer:

x = -1/7

Explanation:

6(4x + 5) = 3(x + 8) + 3​

Distribute

24x+30 = 3x+24 +3

Combine like terms

24x +30 = 3x+27

Subtract 3x from each side

24x-3x +30 = 3x+27-3x

21x +30 = 27

Subtract 30 from each side

21x +30 -30=27-30

21x = -3

Divide by 21

21x/21 = -3/21

x = -1/7

User Vashishth
by
5.2k points